(untitled) (Journal of Architectural Design, 2024)
The formation of tourist centers plays a key role in the development of tourist infrastructure and increasing the attractiveness of historical cities. They ensure not only the preservation of cultural heritage, but also the creation of a modern, comfortable and sustainable space attractive to a wide range of tourists, which contributes to the sustainable development of tourism and the city as a whole.